2014
DOI: 10.1093/cid/ciu296
|View full text |Cite
|
Sign up to set email alerts
|

Practice Guidelines for the Diagnosis and Management of Skin and Soft Tissue Infections: 2014 Update by the Infectious Diseases Society of America

Abstract: A panel of national experts was convened by the Infectious Diseases Society of America (IDSA) to update the 2005 guidelines for the treatment of skin and soft tissue infections (SSTIs). The panel's recommendations were developed to be concordant with the recently published IDSA guidelines for the treatment of methicillin-resistant Staphylococcus aureus infections. The focus of this guideline is the diagnosis and appropriate treatment of diverse SSTIs ranging from minor superficial infections to life-threatenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
1,598
4
147

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,997 publications
(1,767 citation statements)
references
References 222 publications
18
1,598
4
147
Order By: Relevance
“…No RCT could be found that compared the usefulness of achieving early source control in sepsis caused by necrotizing soft tissue infection, although there exist guidelines57, 58 and a review59 on this subject. Although early diagnosis and administration of broad‐spectrum antimicrobials can be effective in improving the prognosis of patients with necrotizing soft tissue infection, when treating patients with organ dysfunction arising from necrotizing soft tissue infection, that is, patients with sepsis, surgical intervention including swift and aggressive drainage of infected lesions is recommended by two different guidelines 57, 58.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…No RCT could be found that compared the usefulness of achieving early source control in sepsis caused by necrotizing soft tissue infection, although there exist guidelines57, 58 and a review59 on this subject. Although early diagnosis and administration of broad‐spectrum antimicrobials can be effective in improving the prognosis of patients with necrotizing soft tissue infection, when treating patients with organ dysfunction arising from necrotizing soft tissue infection, that is, patients with sepsis, surgical intervention including swift and aggressive drainage of infected lesions is recommended by two different guidelines 57, 58.…”
Section: Introductionmentioning
confidence: 99%
“…Although early diagnosis and administration of broad‐spectrum antimicrobials can be effective in improving the prognosis of patients with necrotizing soft tissue infection, when treating patients with organ dysfunction arising from necrotizing soft tissue infection, that is, patients with sepsis, surgical intervention including swift and aggressive drainage of infected lesions is recommended by two different guidelines 57, 58. A review study examining the timing of surgical procedures also suggests that initiating surgery within 24 h after diagnosis can improve the mortality rate by ~20% more than surgeries performed after this period 59.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] Interestingly, a recent prospective cohort study found that 43% of patients were overtreated with parenteral therapy (according to the Clinical Resource Efficiency Support Team [CREST] guidelines), with the authors suggesting that many of these cases could have been managed as outpatients with oral antibiotic therapy. 13 Although studies have been conducted in an effort to identify predictors of admission or prolonged hospital stay, [14][15][16] published clinical trials aiming to predict failure with oral antibiotics for SSTIs are currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Necrotizing fasciitis is a grievous infection of the deeper skin, subcutaneous tissues and fascia [1,2]. It is characterized by extensive and rapidly spreading necrosis and gangrene of the subcutaneous fat and fascia.…”
mentioning
confidence: 99%